Pendidikan Politik melalui Pembelajaran Pendidikan Kewarganegaraan untuk Meningkatkan Kesadaran Politik Siswa - Yohanes Berkhmas Mulyadi; Anyan Anyan (Universitas Kanjuruhan Malang, 2019)
Abstract.This study aims to describe political education through learning civic education to increase the political awareness of students of Kelam Permai 1 High School, Sintang District. This type of research is descriptive, with a qualitative approach. Research subjects were determined by purposive sampling technique. The subject of this study consisted of the Principal, Classroom Teacher, PKn Subject Teacher, Tutor OSIS Teacher, OSIS Chairman and member of Pramuka. Data collection in this study was carried out by observation, indepth interviews and documentation. Data analysis techniques were carried out by data reduction, categorization, display / presentation, and conclusion. The results of this study indicate that to increase students' political awareness, political education is needed through PKn learning. The form of political education through Civics learning in the classroom is role playing, discussion, learning various sources. The benefits of this research are the increased political awareness of students expressed in attitude, good deeds, critical and responsible in carrying out school activities. Keywords: Political education, Student learning, Student political awareness Abstrak Penelitian ini bertujuan mendeskripsikan pendidikan politik melalui pembelajaran pendidikan kewarganegaraan untuk meningkatkan kesadaran politik siswa SMA Negeri 1 Kelam Permai, Kabupaten Sintang.Jenis penelitian ini adalah deskriptif, dengan pendekatan kualitatif. Subjek penelitian ditentukan dengan teknik purposive sampling. Subjek penelitian ini terdiri dari Kepala Sekolah, Guru Wali Kelas, Guru Mata Pelajaran PKn,Pembina OSIS, Ketua OSIS dan anggota Pramuka. Pengumpulan data dalam penelitian ini dilakukan dengan observasi, wawancara mendalam dan dokumentasi.Teknik analisis data dilakukan dengan reduksi data, kategorisasi, display/penyajian, dan pengambilan kesimpulan. Hasil penelitian ini menunjukkan bahwa untuk meningkatkan kesadaran politik siswa, dibutuhkan pendidikan politik melalui pembelajaran PKn. Bentuk pendidikan politik melalui pembelajaran PKn di kelas adalah bermain peran, diskusi, pembelajaran berbagai sumber.Manfaat penelitian ini adalah meningkatnya kesadaran politik siswa yang terekspresi dalam sikap, perbuatan yang baik, kritis dan bertanggungjawab dalam melaksanakan kegiatan sekolah. Kata Kunci: Pendidikan politik, Pembelajaran PKn, Kesadaran Politik